(untitled) (Asian Journal of Social Science Studies, 2022)
The Bangladesh-China-India-Myanmar (BCIM) Economic Corridor is a sub-regional cooperation concept under the framework of the Bangladesh-China-India-Myanmar Regional Cooperation Forum jointly promoted by the governments of China, Bangladesh, India, and Myanmar. It is one of the six important economic corridors under the "One Belt, One Road‖ cooperation initiative. Promoting the construction of the Bangladesh-China-India-Myanmar Economic Corridor will lead to the coordinated development of the three economic regions of East Asia, Southeast Asia, and South Asia. At present, the Bangladesh-China-India-Myanmar Economic Corridor has achieved initial results, but the comparative advantages in the "Belt and Road" have not yet fully manifested. On the basis of analyzing the political mutual trust, interconnection, humanities exchanges, economic and trade exchanges among the four countries, this paper points out that the China-Indian political mutual trust is low, the transportation is in need of renewal, the humanities exchange and cooperation is insufficient, and the intra-regional trade competition increased. In final, the corresponding measures were put forward to promote the construction of the Bangladesh-China-India-Myanmar Economic Corridor under the ―Belt and Road‖.